A novel framework for waste management in smart city transformation with industry 4.0 technologies - Aalok Kumar (Research in Globalization, 2024)
Most of the developed and developing nations focus on the transformation of city livelihood through the development of smart cities. Waste management in smart cities is a critical concern for policymakers and smart city administration. The fourth industrial transformation (hereafter Industry 4.0) helps to improve waste management practices in smart cities to improve the sustainability of the city. This paper tries to develop a roadmap for industry 4.0 technologies relevant to managing waste in smart cities. This paper proposes a novel framework for analyzing the deployment enablers of Industry 4.0 technologies, implementation barriers, current best practices, and opportunities for digital technologies (EBPO) for smart city transformation. The proposed EBPO conceptual framework is analyzed in the context of studies conducted in developed and developing countries. The EBPO presents the unique linkages among the technological advancements for managing waste in smart cities. The present research is an early attempt to explore the relevance of industry 4.0 technologies in the smart waste management context for improving environmental sustainability. The keyword and theme mapping analysis proposes three major waste management clusters in smart cities. This paper provides insight for improving EBPO elements for smart cities' waste management. The policy and theoretical implications are presented for smart city stakeholders. The paper also highlights the different dimensions of the EBPO framework.
Keywords: 330; Industry 4.0; Smart cities; Waste management; Framework development